Successful pregnancy after presurgical uterine artery embolization in the management of a very large cervical myoma: A case report - Suleyman Engin Akhan; Cenk Yasa; Ozlem Dural; Funda Gungor Ugurlucan; Izzet Rozanes (Elsevier, 2022)
Although fibroids are the most common benign tumors of the uterus in women of reproductive age, cervical fibroids are rarely seen. Since cervical fibroids are located deep in the pelvis, the incidence of complications in surgery is high. Among these complications bleeding is the most common, due to poor access to myoma, difficulty in suturing and repair, and distortion of vital neighboring structures. Each case should be managed individually to minimize bleeding. To decrease bleeding in patients who wish to retain their fertility, intraoperative interventions include vasoconstrictors such as vasopressin and adrenaline, uterotonics such as oxytocin, misoprostol or ergometrines, uterine artery clamping, internal iliac artery balloon occlusion catheters, and tourniquets; preoperative interventions include gonadotropin releasing-hormone analogues and uterine artery embolization. We present a case of a 40-year-old woman who had a large cervical myoma and a desire for future fertility. To overcome technical difficulties and reduce intraoperative bleeding during myomectomy, presurgical uterine artery embolization was performed. The patient conceived spontaneously after the operation and a healthy baby was delivered by cesarean section.